A critical reflection on the inclusion of spatial thinking in undergraduate Geography modules: A case study of selected South African universities (The Journal of Geography Education in Africa, 2024)
This research reflects on the nature of spatial thinking as featured in undergraduate Geography modules at South African universities and explores ways of enhancing its role. The research has three objectives: to identify Geography modules that include spatial thinking in their curricula, to determine whether the lecturers of these modules consider the concept of spatial thinking when developing new modules and to evaluate the spatiality of the outcomes of the selected modules by assessing it against the taxonomy of spatial thinking. Generally, the spatiality of the module outcomes and the integration level of the three components of spatial thinking into the modules which were considered proved to be limited. Not one of the departments offering these modules was observed to set a clear developmental path to foster the development of students' spatial thinking skills. When developing Geography modules, more attention should be given to incorporating spatial thinking into the curriculum. Every effort should be made at departmental level to ensure that students' spatial thinking skills are adequately developed during the course of their studies.
Keywords: Spatial thinking; module outcomes; South African universities; Geography; Geography modules; undergraduate